2019
DOI: 10.1016/j.jagp.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Follow-Up Rate After Psychiatric Hospitalization of Medicare Beneficiaries by Hospital Characteristics and Social Determinants of Health

Abstract: Hospitals have considerable opportunity to improve the quality of their transitional care processes and increase the percentage of Medicare patients receiving timely mental health follow-up after discharge. Policymakers should consider strengthening the incentives for hospital performance on these quality measures while working to improve the behavioral health infrastructure of minority communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…These rates are similar to follow up-rates reported for Black (40.0%) and non-Hispanic White (50.9%) ED patients, and on par with the recently reported 30% seven-day follow-up rate in psychiatric patients after discharge from inpatient hospitalization. 31,32 This potential for difficult follow-up, coupled with the murky legal waters of consenting patients to enroll in a study while actively suicidal, were primary considerations in our decision to evaluate the feasibility of CALM-ED prior to attempting a randomized control trial into whether CALM leads to improved safe storage in suicidal patients.…”
Section: Limitationsmentioning
confidence: 99%
“…These rates are similar to follow up-rates reported for Black (40.0%) and non-Hispanic White (50.9%) ED patients, and on par with the recently reported 30% seven-day follow-up rate in psychiatric patients after discharge from inpatient hospitalization. 31,32 This potential for difficult follow-up, coupled with the murky legal waters of consenting patients to enroll in a study while actively suicidal, were primary considerations in our decision to evaluate the feasibility of CALM-ED prior to attempting a randomized control trial into whether CALM leads to improved safe storage in suicidal patients.…”
Section: Limitationsmentioning
confidence: 99%
“…51 Furthermore, most of our patients were of low to average socioeconomic status, supporting the view that socioeconomic status may affect readmission rate. 7,13,54 In the present study, psychotic spectrum disorder was the most common diagnosis, followed by mood disorder. Morris et al 34 identified psychotic disorders in 26%, mood disorders in 36% and substance use disorders in 51% of patients readmitted to the emergency department within 30-day post-discharge.…”
Section: Discussionmentioning
confidence: 50%
“…Providing follow-up after psychiatric hospitalization discharge has proven useful to reduce risk of non-adherence to medication and suicide [13,14]. Telepsychiatry may facilitate timely delivery of follow-up care after discharge and make it easier to support patients' adherence to treatment [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…However, only 55.8% of hospitals delivered timely care following psychiatric hospitalization, with psychiatric specialty hospitals, public hospitals, and minorityserving hospitals reporting lower follow-up rates within 30 days post discharge [16].…”
Section: Introductionmentioning
confidence: 99%